9x=10-3(5x-6)

Simple and best practice solution for 9x=10-3(5x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x=10-3(5x-6) equation:



9x=10-3(5x-6)
We move all terms to the left:
9x-(10-3(5x-6))=0
We calculate terms in parentheses: -(10-3(5x-6)), so:
10-3(5x-6)
determiningTheFunctionDomain -3(5x-6)+10
We multiply parentheses
-15x+18+10
We add all the numbers together, and all the variables
-15x+28
Back to the equation:
-(-15x+28)
We get rid of parentheses
9x+15x-28=0
We add all the numbers together, and all the variables
24x-28=0
We move all terms containing x to the left, all other terms to the right
24x=28
x=28/24
x=1+1/6

See similar equations:

| 4(3x+9)=-14+26 | | x(15+8+180+x)=13000 | | 18=3(k−11) | | 7/12=k/8 | | -8=-4(w−14) | | 6y+14=36 | | d+5d=12 | | 5u-8=-33 | | 3.5=x(x+3) | | 6z/7-5z/9=1 | | -8+p/3=-4 | | 64x2-48x=183 | | 8+p=-2p+3 | | 5(x+12)=1/2(7+10x) | | 1/2x+1/10x+1/20x)-x=35,000 | | -5b-6+4b=0 | | -5b-6+4=0 | | (3a-5)=(6a-7) | | 8-5n=9 | | -5x-(-7x-4x)=-2(3x-4) | | 11x+20x-9+5=-5x+5-9 | | 1b/8+1/7=17 | | 500+x(20)=2900 | | 500+x(20)=5300 | | 29x-(x-27)=13+7(5x+1) | | -14(z-5=14z+70 | | 200=x2+25 | | x2+1(x)=1 | | 0.5-h=2-h | | 3=5x+4-6 | | 2w+2w+16=76 | | 4(a–2)=12 |

Equations solver categories